EFFECT OF NATURE SOUND THERAPY ON THE LEVEL OF CORTISOL IN POSTPARTUM PRIMIPARA - Yulinda Laska; Suryono Suryono; Melyana Nurul Widyawati; Ari Suwondo; Suryati Kusworowulan (Belitung Nursing Journal, 2018)
Background: Majority of primiparous mothers experience a wide range of postpartum blues, which leads to stress and an increase in cortisol. Therefore, efforts to reduce cortisol level is needed. Nature sound music therapy is believed to make the mothers feel relaxed and comfortable. Objective: To examine the effect of the nature music therapy on cortisol levels in postpartum primipara. Methods: This was a true experimental study with pretest-posttest control group design. The study was conducted in the postpartum ward in the General Hospital of Semarang Indonesia from November 2016 to January 2017. There were 39 postpartum primipara selected in this study using simple random sampling divided into three groups: 1) the experiment group who received the nature music therapy for 15 minutes, 2) the experiment group who received the nature music therapy for 30 minutes, and 3) the control group. One-way ANOVA test was performed for data analysis. Results: There was a statistically significant effect of the nature sound therapy on the cortisol level in the postpartum primipara, with p-value = 0.010 (<0.05). Conclusion: There was a significant effect of the nature music therapy on the cortisol levels in postpartum primipara. Thus, the application of nature music therapy can be an alternative therapy especially for postpartum primipara who experience emotional stress, physical, anxiety, and fatigue.